Peranan Kecerdasan Emosional terhadap Penyesuaian Diri dan Perilaku Delinkuen pada Remaja di Yogyakarta - Aziz, Rahmat (ULUL ALBAB Jurnal Studi Islam, 2001)
The term emotional quotion is relatively new in psychology and it is assumed to play significant role in daily life. This research finds out that emotional intelligence can be used as predictor for personal adjustment and behavorial delinquent in adolescent. The finding of this study shows that: first, emotional intelligence and requirements for adolescents in Yogyakarta City are relatively low, while the tendency to behave delinquently is relatively high. Second, there is a positive relationship between emotional intelligence and negative relationships with delinquency behavior. Third, there is no significant difference between male and female teenagers in terms of emotional and individual intelligence, but there are problems in delinquency behavior, women who do higher to behave delinquently if the opposite is with men.